Методика и результаты эксергетического анализа различных схем энергоустановок на биогазе - Мазуренко, А. С.; Денисова, А. Е.; Климчук, А. А.; Нго Минь Хиеу (НТУ "ХПИ", 2014)
Рассмотрены принципиальные тепловые схемы различных биогазовых энергоустановок и выполнен анализ перспектив их использования. Представлена методика эксергетического анализа различных схем биогазовых установок, выполнено сопоставление параметров циклов рассматриваемых установок, приведен расчет и анализ эксергетических характеристик газотурбинной установки, парогазовой установки со сбросом газов в котел и парогазовой установки с высокотемпературным парогенератором и промежуточным перегревом пара.

The methods of the exergic analysis of different circuits of biogas power plants that allow for the replacement of the traditional types of energy and improvement of the environmental conditions have been presented. Schematic heat diagrams of biogas units have been proposed and their efficiency has been analyzed. The cycle parameters of different biogas units (gas turbine unit, steam gas unit with the gas vent to the boiler and the steam gas unit with high temperature steam generator and intermediate steam overheating have been compared and their exergic characteristics have also been compared. The exergic analysis proved that the cycle of the biogas steam gas unit with the intermediate steam overheating using the high–pressure steam generator is the most efficient, which is explained by the fact that the fraction of the thermal energy of combustion products for the steam cycle and gas cycle is approximately the same in contrast to traditional steam and gas units.
Methods and results of the exergic analysis of different circuits of biogas power plants
Keywords: газотурбинная установка; эксергетические характеристики; exergic characteristics; gas turbine unit; intermediate steam heating